Precision Analysis of Height Measurements Realized on Ballastless Track - Jana Izvoltova; Peter Pisca; Andrej Villim; Marian Mancovic (Communications - Scientific letters of the University of Zilina, 2014)
The ballastless track is a relatively new track construction built in Slovak Railways. The Department of Geodesy and the Department of Railway Building and Track Management of the University of Zilina have been involved in the research project aimed to monitor such an unconventional track construction. The periodical diagnostics of the vertical and positional geometrical track parameters is realized by absolute and relative methods to determine the construction conditions under traffic loading. Precision analysis of the observation is necessary to define confidential interval of measurements errors.